Recurrent gestational diabetes : Breaking the transgenerational cycle with lifestyle modification. - Liney,T; Shah,NM; Singh,N (Wien Klin Wochenschr, 2022)
PURPOSE: This literature review is aimed at examining the benefits of lifestyle modifications in preventing recurrent gestational diabetes (GDM). Worldwide GDM affects approximately 16.2% of all pregnancies with significant maternal, fetal and neonatal complications. Almost two thirds of pregnant women with GDM will develop type 2 diabetes mellitus (T2DM) in the years following pregnancy. The proportion of women affected by GDM is on the rise and reflects increasing trends in T2DM as well as adult and childhood obesity. METHODS: Using predefined subject headings, we searched for relevant articles from the PubMed, Scopus, and Cochrane databases. RESULTS: For high-risk women lifestyle modifications, such as dietary and exercise changes, are the mainstay of treatment to reduce negative outcomes for both women and their pregnancies. This includes reducing the incidence of recurrent GDM and future T2DM by intervening during pregnancy and in the postnatal period. CONCLUSION: This review provides an overview of the literature to date, discusses different targeted approaches and how these interventions can optimise their benefits, and where further research is required.